Weak Form Efficiency of Cryptocurrency and Precious Metal Market in the Midst of Covid-19 Pandemic - Dilla Andharini; Robiyanto Robiyanto; Harijono Harijono (Politeknik Caltex Riau, 2022)
Precious metals and cryptocurrencies are one of the most preferred investment instruments during the Covid-19 pandemic. There are three types of market efficiency, weak form efficiency, semi-strong, and strong form efficiency; this is disclosed in the efficient market hypothesis proposed by Fama in several of his works. Efficient or inefficient market can be seen from the returns obtained by the market participants, market participants will get a reasonable return if they are in an efficient market. This study aims to determine whether the precious metals and cryptocurrency markets are efficient in the weak form. Run test and Augmented Dickey-Fuller test are used to determine the randomness of price movements (random walk). The more random the price, the more efficient it will be in the weak form. The period used in this study is January 1, 2019 to June 30, 2021. The results of this study are the price of precious metals runs randomly during the Covid-19 pandemic, which means that the precious metal market is efficient in a weak form. Meanwhile, the results of the cryptocurrency return test show that the cryptocurrency market is inefficient in the weak form during the Covid-19 pandemic.